The Influence of Human Resources Quality, Job Placement, and Competence on the Performance of Employees in the Regional Secretariat Section of PP Aru Regency - Tomasoa, Lidya; Latupapua, Conchita V.; Leuhery, Ferdy (SEAN Institute, 2024)
This research aims to determine the influence of human resource quality, job placement and competency on the performance of PP Aru District Regional Secretariat employees. The sample in this research was 58 employees of the Regional Secretariat of PP Aru Regency, using a sampling technique, namely the probability sampling method. The analytical method used is multiple linear regression analysis assisted by the SPSS Ver.22.00 test tool. The results of this research show that developing human resource capacity, work placement and competency has a positive and significant effect on the performance of Aru district regional secretariat employees.